1. First, we need to approximate <em>the radius</em>. That is the distance from that middle point to the edge. The broom is about half the distance. That means that the radius is about <em>10 feet</em>. Also, multiplying the radius by π will get you nowhere. To find the area, you need to use the equation <em>A = πr²</em>. We know know that r = 10, so 10²π ≈ 100 * 3.1 = 310 ft².
2. Complementary angles <em>add up to 90°, which forms a right angle</em>. Supplementary angles <em>add up to 180°, which forms a straight angle, or a line</em>. We can ignore A and B, since there isn't any right angles. Also, ∠RVS makes a straight line with ∠SVT and ∠RVU. From our options, we can see that C has the fitting description.
Your answer is 3/7 because you have to go 5-5=0 and 5/7-2/7=3/7 so it is 3/7
Answer:
Step-by-step explanation:
Let x represent the number of attendees that it will take the company to break even.
The company pays a flat fee of $98 to rent a facility in which to hold each session. Additionally, for every attendee who registers, the company must spend $16 to purchase books and supplies. This means that the total cost that the company would pay for x attendees is
16x + 98
Each attendee will pay $65 for the seminar. This means that the total revenue that the company would generate from x attendees is 65x.
At the break even point,
total cost = total revenue
Therefore,
16x + 90 = 65x
65x - 16x = 98
49x = 98
x = 98/49
x = 2
It will take 2 attendees and the total expenses and revenues is
2 × 65 = $130
Answer:
1. reflection across x-axis
2. translation 6 units to the right and 3 units up (x+6,y+3)
Step-by-step explanation:
The trapezoid ABCD has it vertices at points A(-5,2), B(-3,4), C(-2,4) and D(-1,2).
First transformation is the reflection across the x-axis with the rule
(x,y)→(x,-y)
so,
- A(-5,2)→A'(-5,-2)
- B(-3,4)→B'(-3,-4)
- C(-2,4)→C'(-2,-4)
- D(-1,2)→D'(-1,-2)
Second transformation is translation 6 units to the right and 3 units up with the rule
(x,y)→(x+6,y+3)
so,
- A'(-5,-2)→E(1,1)
- B'(-3,-4)→H(3,-1)
- C'(-2,-4)→G(4,-1)
- D'(-1,-2)→F(5,1)
Answer:
The product of the other two zeros is c
Step-by-step explanation:
Let α, β and γ be the zeros of the polynomial x³ + ax² + bx + c. Since one of the zeros is -1, therefore let γ = -1. Hence:
sum of the roots = α + β + γ = -a
-1 + β + γ = -a
β + γ = -a + 1
αβ + αγ + βγ = b
-1(β) + (-1)γ + βγ = b
-β -γ + βγ = b
Also, the product of the zeros is equal to -c, hence:
αβγ = -c
-1(βγ) = -c
βγ = c
Hence the product of the other two zeros is c